Islam's Jesus - Saritoprak, Zeki. (Gainesville : University Press of Florida, 2014)
While it is not well known among Christians, Jesus has an important role in the Quaranic literature, and this book examines this provocative topic, focusing on Jesus's role in the eschatology of Islam, especially on the afterlife.
The Qur'an and Jesus as God's messenger -- A Qur'anic perspective on the eschatological role of Jesus -- Islamic eschatology and Jesus as a sign of the hour -- The Hadith and Jesus's eschatological descent -- Speculations about Jesus's return -- The Mahdi and Jesus as allies against al-Dajjal (the Antichrist) -- Literalist approaches to Jesus's eschatological role in Islamic theology -- Symbolic, allegorical, and other interpretive approaches to Jesus's eschatological role -- Jesus's descent and theologies of Muslim-Christian cooperation.
Includes bibliographical references (pages 203-214) and index.
Keywords: Jesus Christ -- In the Qur'an.; Jesus Christ -- Islamic interpretations; Qur'an -- Relation to the Bible; Islam -- Relations -- Christianity; Christianity and other religions -- Islam